Práticas de sustentabilidade na cadeia de suprimentos multicamadas na avicultura de corte - Santos, Karina Aparecida dos (2022)
An alternative point of view is presented to understand Sustainability in the Multi-Tier Supply Chain (SCSM). It therefore suggests a practice-based approach to sustainability for the MultiTier Supply Chain (CSM), combined with a vision of knowledge management and learning about sustainability. Theories of Practice (TP) can provide a theoretically propositional and critical logic on how to build and maintain sustainability in CSM. Understanding that sustainability is something that must be put into practice by agents, actions, and structures, and must be done over time. But the vision of sustainability practiced is in line with what people do in organizations, meeting a demand in studies that focus on micro-level issues in the chain. Therefore, this thesis is anchored in the central argument that the practice of sustainability is possible in CSM if this practice is recognized, meant and learned by the various actors involved. The thesis, composed of three articles, makes an initial contribution (Article 1) identifying how SCSM studies have evolved in recent years, considering theories, configurations and methodologies used. From a Systematic Review of Literature (Article 2) to empirically investigate, through a case study, the elements of sustainability practice and how they are practiced in an inter- and intraorganizational context in the CSM; and finally, (Article 3) understand sub-suppliers form knowledge and learn sustainability practices in a multi-layered context. In an ethnographic study. Our findings show that the practice of sustainability is possible if it is constant and based on shared values and principles. This challenge may be greater in CSM, where meaning is deflected and reconstructed in the chain. Factors such as learning, skills and knowledge are grounded in the meaning of shared practices. If such meanings and values are not properly incorporated and understood, the propensity for risks and unsustainable conduct becomes greater. Thus, compromising sustainability in the chain. While the leading company maintains the core commitment to sustainability, it is not essentially that its suppliers and sub-suppliers embody the same commitment. Having elements of the practice does not necessarily suggest that there is a practice being practiced.